Dynamic Geometry Study as a Learning Visualization Tool in the Digital Era - Duma, Sonny Yaitu; Modjo, Ardiyanto Saleh (Aksioma Education Journal, 2025)
In the digital era, the integration of technology in education is becoming increasingly important to improve the effectiveness of learning. One significant innovation in mathematics education is the use of dynamic geometry through software such as GeoGebra and Cabri Geometry. This technology allows students to visualize and explore geometric concepts interactively, so that they can better understand spatial relationships. This approach is in line with constructivism theory which emphasizes exploration-based learning and direct experience. Various studies have shown that the use of dynamic geometry not only improves conceptual understanding but also develops critical and analytical thinking skills. However, the implementation of this technology faces several challenges, such as the readiness of educators to integrate the software into learning strategies and the limited infrastructure in some educational institutions. Therefore, continuous training is needed for educators and educational policies that support the wider adoption of this technology. With the right implementation strategy, dynamic geometry can be a revolutionary learning tool in mathematics education, increasing student engagement, and strengthening their spatial literacy and problem-solving skills in the digital era.